2002
DOI: 10.1002/mus.10046
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative changes in acetylcholine receptor distribution at the neuromuscular junction following free muscle transfer

Abstract: The qualitative and quantitative changes in acetylcholine receptor distribution were studied in the gracilis muscle of the Wistar rat following free neurovascular transfer. Even at 30 weeks after transfer, the morphology of the neuromuscular junction failed to return to the presurgical state. The number of acetylcholine receptors at the reinnervated neuromuscular junction also remained lower than the control. The persistent weakness following free neurovascular muscle transfer may be attributed to these qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…It has been previously proposed that the morphological and functional state of AChRs in muscle fibers is closely correlated with the affiliated innervation 25. This hypothesis had been supported by the study of spinal nerve crush injury model in rats, which showed that AChRs at end plates had crispation, depressed density, disordered structure, and disaggregation through the α‐bungarotoxin fluorescent binding agent staining 26. The degree of the nerve damage was in accordance with the extent of AChR impairment and with the level of muscle weakness.…”
Section: Discussionmentioning
confidence: 83%
“…It has been previously proposed that the morphological and functional state of AChRs in muscle fibers is closely correlated with the affiliated innervation 25. This hypothesis had been supported by the study of spinal nerve crush injury model in rats, which showed that AChRs at end plates had crispation, depressed density, disordered structure, and disaggregation through the α‐bungarotoxin fluorescent binding agent staining 26. The degree of the nerve damage was in accordance with the extent of AChR impairment and with the level of muscle weakness.…”
Section: Discussionmentioning
confidence: 83%
“…21 Although the number of AChRs at the reinnervated neuromuscular junction of transferred muscle flap was studied, 11 this study focused on the correlation between contractile function recovery and changes of AChR and expression of its subunits of transferred muscle flap.…”
Section: Discussionmentioning
confidence: 99%
“…The number of acetylcholine receptors at the reinnervated neuromuscular junction was found still remained lower 30 weeks after transfer. 10,11 The AChR is an integral membrane channel protein, that is, a key element in cholinergic synaptic transmission. Experimental studies have demonstrated that mammalian muscle mainly expressed two subunits of AChR channels, a low conductance fetal subunit AChRg and a high conductance adult subunit AChRe.…”
mentioning
confidence: 99%